The Review Study of Environmental Education Curriculum in Climate Change Mitigation - Zulfia Hanum Alfi Syahr; Dian Hafit Syaifullah; Buyamin Buyamin; Novian Uticha Sally (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Indonesia is a country whose geographical location is on the equator, has many islands and tropical forest areas, and is surrounded by volcanoes. Indonesia also has a high potential for natural disasters, such as volcanic eruptions, floods, tsunamis, forest fires, etc. Therefore, it is necessary to introduce early on how to mitigate and adapt to disasters due to climate change. Through education, integrating mitigation and adaptation to climate change will get along with the national education curriculum in Indonesia. The problem in this study is how the concepts of climate change mitigation and adaptation learning models can integrate into the national education curriculum in Indonesia. The goal is to find an ideal model framework for implementing climate change mitigation and adaptation lessons in the national education curriculum. The method used is qualitative, with a literature study of articles indexed in Scopus. The results obtained are that the integrated model of climate change mitigation and adaptation learning can be carried out in several stages, namely: 1) mapping the types of disasters and their mitigation measures; 2) linking knowledge about climate change mitigation and adaptation with real examples; 3) inserting climate change mitigation and adaptation material into various subjects in schools.